2008
DOI: 10.1002/psc.1042
|View full text |Cite
|
Sign up to set email alerts
|

A photoswitchable thioxopeptide bond facilitates the conformation‐activity correlation study of insect kinin

Abstract: Thioxopeptide bond psi[CS-N], a nearly isosteric modification of the native peptide bond, was introduced into insect kinin active core pentapeptide to evaluate the impact of backbone cis/trans photoswitching on bioactivity. The thioxo analog Phe(1)-Tyr(2)-psi[CS-N]-Pro(3)-Trp(4)-Gly(5)-NH(2) (psi[CS-N](2)-kinin), was synthesized by Fmoc solid-phase peptide strategy. The reversible photoswitching property was characterized via spectroscopic methods and HPLC, which showed that the cis conformer increased from 15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 53 publications
1
29
0
Order By: Relevance
“…For example, the cis/trans prolyl peptide bond isomerization during collagen folding could be modulated by exploiting the tendency of thioamides to isomerize upon UV radiation. 24,50,51 In addition, thioamide-containing CMPs could be useful in high-throughput assays of collagen binding by accessing the ability of thioamides to quench pendant fluorophores. 52 Finally, thioamides are protease-resistant, 53 making thioamide-incorporation a potential strategy for producing robust collagen-based biomaterials.…”
mentioning
confidence: 99%
“…For example, the cis/trans prolyl peptide bond isomerization during collagen folding could be modulated by exploiting the tendency of thioamides to isomerize upon UV radiation. 24,50,51 In addition, thioamide-containing CMPs could be useful in high-throughput assays of collagen binding by accessing the ability of thioamides to quench pendant fluorophores. 52 Finally, thioamides are protease-resistant, 53 making thioamide-incorporation a potential strategy for producing robust collagen-based biomaterials.…”
mentioning
confidence: 99%
“…The CD spectrum of a 5‐mer endothioxopeptide analog of the insect kinin active core exhibits a 25% variation in the intensity of its 276 nm CD band after trans / cis phototriggered isomerization . This finding suggests that the conformation around the C(S)NH chromophore changes remarkably upon UV irradiation.…”
Section: Resultsmentioning
confidence: 97%
“…The CD spectrum of a 5-mer endothioxopeptide analog of the insect kinin active core exhibits a 25% variation in the intensity of its 276 nm CD band after trans/cis phototriggered isomerization. [116] This finding suggests that the conformation around the AC(@S)ANHA chromophore changes remarkably upon UV irradiation. A thermal melting CD study of a 12-mer, mono-thionated Trp-zip variant indicated that its overall b-hairpin conformation is not significantly perturbed upon a single thionamide incorporation, but, when this mutation is close to the terminal regions, the energetic destabilization is even more reduced (the ends of b-hairpins are frayed).…”
Section: Circular Dichroismmentioning
confidence: 91%
“…A similar result was reported for the functional interaction between thioxylated kinin and its receptor. [68] Thioxo and selenoxo [69] modifications establish valuable triggers for the proven cis/trans switching mechanism. The principle limitation is that the isomerizing groups must be introduced by synthetic methods and this restricts their placement to peptides or very small proteins.…”
Section: Limited Structural Rearrangementmentioning
confidence: 99%